The impact of the solar energy collecting systems on an individual agricultural household - Petruţa Turek-Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Using solar energy through photovoltaic systems implementation in an agricultural household leads to the increasing of it's efficiency, to optimizing energy balance thus implying the decreasing of the primary energy costs. The solar energy refers to a renewable energy source that is produced directly by light and solar radiation. It can be used to generate electricity through solar cells (photovoltaic); to generate electricity through thermal power plants; to generate electricity through solar towers,etc. The introduction and development of new technologies and processes through the use of energy from renewable sources leads to production costs reduction and implicitly to the increase of ecomonic profitability of the agricultultural holding.
Keywords: 330; renewable energy; solar energy; photovoltaic panels